Circulating CD34+ Cells: A New Biomarker of Residual Pulmonary Vascular Obstruction after Pulmonary Embolism - Nicolas Gendron; Benjamin Planquette; Anne Roche; Richard Chocron; Dominique Helley; Aurélien Philippe; Pierre-Emmanuel Morange; Pascale Gaussem; Olivier Sanchez; David M. Smadja (Stem Cell Reviews and Reports, 2025)

VEGF-A plasma levels are associated with impaired DLCO and radiological sequelae in long COVID patients - Aurélien Philippe; Sven Günther; Jeanne Rancic; Pauline Cavagna; Bertrand Renaud; Nicolas Gendron; Elie Mousseaux; Thông Hua-Huy; Guillaume Reverdito; Benjamin Planquette; Olivier Sanchez; Pascale Gaussem; et al. (Angiogenesis, 2024)

Improving Autologous Fat Grafting in Regenerative Surgery through Stem Cell-Assisted Lipotransfer - Benjamin Debuc; Nicolas Gendron; Audrey Cras; Jeanne Rancic; Aurélien Philippe; Curtis L. Cetrulo; Alexandre G. Lellouch; David M. Smadja (Stem Cell Reviews and Reports, 2023)

Von Willebrand factor collagen-binding capacity predicts in-hospital mortality in COVID-19 patients: insight from VWF/ADAMTS13 ratio imbalance - Aurélien Philippe; Nicolas Gendron; Olivier Bory; Agathe Beauvais; Tristan Mirault; Benjamin Planquette; Olivier Sanchez; Jean-Luc Diehl; Richard Chocron; David M. Smadja (Angiogenesis, 2021)

Circulating Von Willebrand factor and high molecular weight multimers as markers of endothelial injury predict COVID-19 in-hospital mortality - Aurélien Philippe; Richard Chocron; Nicolas Gendron; Olivier Bory; Agathe Beauvais; Nicolas Peron; Lina Khider; Coralie L. Guerin; Guillaume Goudot; Françoise Levasseur; Christophe Peronino; Jerome Duchemin; et al. (Angiogenesis, 2021)

Multidimensional Proteomic Approach of Endothelial Progenitors Demonstrate Expression of KDR Restricted to CD19 Cells - Coralie L. Guerin; Léa Guyonnet; Guillaume Goudot; Dominique Revets; Maria Konstantinou; Anna Chipont; Richard Chocron; Adeline Blandinieres; Lina Khider; Jeanne Rancic; Christophe Peronino; Benjamin Debuc; et al. (Stem Cell Reviews and Reports, 2021)

Angiopoietin-2 as a marker of endothelial activation is a good predictor factor for intensive care unit admission of COVID-19 patients - David M. Smadja; Coralie L. Guerin; Richard Chocron; Nader Yatim; Jeremy Boussier; Nicolas Gendron; Lina Khider; Jérôme Hadjadj; Guillaume Goudot; Benjamin Debuc; Philippe Juvin; Caroline Hauw-Berlemont; et al. (Angiogenesis, 2020)

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.